Subsets of Eosinophils in Asthma, a Challenge for Precise Treatment - Novosad, Jakub; Krčmová, Irena; Souček, Ondřej; Drahošová, Marcela; Sedlák, Vratislav; Kulířová, Martina; Králíčková, Pavlína (International journal of molecular sciences, 2023)
The existence of eosinophils was documented histopathologically in the first half of the 19th century. However, the term "eosinophils" was first used by Paul Ehrlich in 1878. Since their discovery and description, their existence has been associated with asthma, allergies, and antihelminthic immunity. Eosinophils may also be responsible for various possible tissue pathologies in many eosinophil-associated diseases. Since the beginning of the 21st century, the understanding of the nature of this cell population has undergone a fundamental reassessment, and in 2010, J. J. Lee proposed the concept of "LIAR" (Local Immunity And/or Remodeling/Repair), underlining the extensive immunoregulatory functions of eosinophils in the context of health and disease. It soon became apparent that mature eosinophils (in line with previous morphological studies) are not structurally, functionally, or immunologically homogeneous cell populations. On the contrary, these cells form subtypes characterized by their further development, immunophenotype, sensitivity to growth factors, localization, role and fate in tissues, and contribution to the pathogenesis of various diseases, including asthma. The eosinophil subsets were recently characterized as resident (rEos) and inflammatory (iEos) eosinophils. During the last 20 years, the biological therapy of eosinophil diseases, including asthma, has been significantly revolutionized. Treatment management has been improved through the enhancement of treatment effectiveness and a decrease in the adverse events associated with the formerly ultimately used systemic corticosteroids. However, as we observed from real-life data, the global treatment efficacy is still far from optimal. A fundamental condition, "sine qua non", for correct treatment management is a thorough evaluation of the inflammatory phenotype of the disease. We believe that a better understanding of eosinophils would lead to more precise diagnostics and classification of asthma subtypes, which could further improve treatment outcomes. The currently validated asthma biomarkers (eosinophil count, production of NO in exhaled breath, and IgE synthesis) are insufficient to unveil super-responders among all severe asthma patients and thus give only a blurred picture of the adepts for treatment. We propose an emerging approach consisting of a more precise characterization of pathogenic eosinophils in terms of the definition of their functional status or subset affiliation by flow cytometry. We believe that the effort to find new eosinophil-associated biomarkers and their rational use in treatment algorithms may ameliorate the response rate to biological therapy in patients with severe asthma.
Keywords: eozinofily; asthma; biological therapy; alergie; počet leukocytů; lidé; Leukocyte Count; biomarkers; Hypersensitivity; eosinophils; biologické markery; immunophenotype; bronchiální astma; Biomarkers; Eosinophils; Asthma; Humans